COVID-19: Update on Its Ocular Involvements, and Complications From Its Treatments and Vaccinations. Issue 6 (November 2021) - Lin, Timothy P.H.; Ko, Chung-Nga; Zheng, Ke; Lai, Kenny H.W.; Wong, Raymond L.M.; Lee, Allie; Zhang, Shaochong; Huang, Suber S.; Wan, Kelvin H.; Lam, Dennis S.C.
Abstract : Abstract: The coronavirus disease 2019 (COVID-19) came under the attention of the international medical community when China first notified the World Health Organization of a pneumonia outbreak of then-unknown etiology in Wuhan in December 2019. Since then, COVID-19 caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has appalled the world by spreading at a pandemic speed. Although ophthalmologists do not directly engage in the clinical care of COVID-19 patients, the ophthalmology community has become aware of the close ties between its practice and the pandemic. Not only are ophthalmologists at heightened risk of SARS-CoV-2 exposure due to their physical proximity with patients in routine ophthalmic examinations, but SARS-CoV-2 possesses ocular tropism resulting in ocular complications beyond the respiratory tract after viral exposure. Furthermore, patients could potentially suffer from adverse ocular effects in the therapeutic process. This review summarized the latest literature to cover the ophthalmic manifestations, effects of treatments, and vaccinations on the eye to aid the frontline clinicians in providing effective ophthalmic care to COVID-19 patients as the pandemic continues to evolve.